Solvent selection for efficient extraction of bioactive compounds from grape pomace - Pintać, Diandra; Majkić, Tatjana; Torović, Ljilja; Orčić, Dejan; Beara, Ivana; Simin, Nataša; Mimica–Dukić, Neda; Lesjak, Marija (Industrial crops and products, 2018)
[Display omitted] •Efficacy of 6 solvents for natural products extraction from grape pomace was studied.•Ethyl acetate is the most efficient solvent for a wide range of phenolic classes.•Acidified 50% methanol proved to be the best option for extraction of anthocyanins.•Pomaces contain high amounts of triterpenoid ursolic acid, efficiently extracted with acetone.•80% MeOH is best for obtaining highest yield of phenolics for large scale industries. Pomace is a winemaking by-product, rich in bioactive compounds which exert various health benefits and are used as dietary supplements, cosmetic ingredients, food colorants and preservatives. Isolation and further utilization of these compounds is an important issue in pomace waste management. Different industries have different requirements for specific classes of compounds and thus, selective extraction methods for isolation of these classes should be developed. In this work, the efficacy of six solvents (80% MeOH, 80% EtOH, EtOAc, acetone, acidified 50% and 80% MeOH) for the extraction of polyphenolic and triterpenoid compounds was examined. Pomaces of different grape varieties from Fruška Gora winery region in Serbia were used for extraction. 47 phenolics and 3 triterpenoids were analyzed by LC–MS/MS and 5 anthocyanin glucosides by LC-UV/VIS, while contents of total phenols and flavonoids were determined spectrophotometrically in obtained extracts. The most efficient solvent for each class and each compound was defined: EtOAc was the best for obtaining an extract rich in polyphenols, acidified 50% MeOH for isolation of anthocyanins, and acetone for ursolic acid. For industries that work on a large scale and aim at the highest utilization of raw material, 80% MeOH was found to be a solvent of choice, providing the highest yield of all polyphenols. This study confirmed that pomaces from Fruška Gora vineyards are a promising source of bioactive compounds, suggesting that their utilization could be very attractive for pharmaceutical, food and cosmetic industries.